A reconfigurable stacked patch microstrip array antenna / Nurulazlina Ramli - Ramli, Nurulazlina (Institute of Graduate Studies, UiTM, 2015)
The rapid development of wireless communication systems in recent years has created a strong need for the development of new antenna structures. In this context, reconfigurable antennas have become very attractive for modern wireless communications because they allow the use of a single antenna for multiple systems. The research described in this thesis introduces the concept of reconfigurable antennas that are capable to operate at two different operating frequencies, either at 2.6 GHz or 3.5 GHz and were able to switch their beam control to various patterns. At the early stage of this project, a new frequency reconfigurable antenna design namely Aperture Coupler - Reconfigurable Stacked Patch Microstrip Antenna (AC-FRSPMA) of Structure 1 and Structure 2 with different substrate materials was constructed. It uses a combination of aperture-coupled technique and stacked patch for the radiating elements to reduce the spurious radiation and increase the bandwidth performance. These designs successfully achieved frequency reconfigurability by implementing new coupling methods in the aperture coupled technique. The used of C-foam material in Structure 2 contributed to the high gain performance as compared to Structure 1 due to its characteristics which is similar to air. Then, by applying these concepts, three new reconfigurable antenna designs which can operates either at 2.6 GHz (WiMAX) or 3.5 GHz (LTE)…